(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
For much of human history, weather has been regarded as one of nature’s greatest uncertainties. Storms, droughts, floods, and heat waves have always occurred, shaping civilizations, influencing agriculture, and challenging societies. Today, however, scientists are observing a profound transformation in the Earth’s climate system. Weather events that were once considered statistically rare are becoming increasingly frequent and more intense. This shift has prompted extensive scientific investigation into one of the defining questions of the twenty-first century: how is climate change influencing extreme weather?